Catalyst-free one-pot, four-component approach for the synthesis of di- and tri-substituted N-sulfonyl formamidines. Issue 25 (27th April 2021) - Liu, Ai-Ran; Zhang, Lei; Li, Jiao; Wusiman, Abudureheman
Abstract : We report a one-pot, four-component catalyst-free strategy for the synthesis of di- and tri-substituted N -sulfonylformamidines, from simple, widely-available precursors. Abstract : A straightforward one-pot, multicomponent approach was developed to synthesize di- and tri-substituted N -sulfonyl formamidines from sulfonyl chlorides, NaN3, ethyl propiolate, and primary/secondary amines under mild conditions without catalysts or additives. Structural analysis of the di-substituted sulfonyl formamidines indicated formation of the E-syn / anti isomeric form. Tri-substituted analogues only formed E -isomers.